Introduction to crowd science - Still, G. Keith (CRC Press, 2013)
This well-grounded and practical guide highlights the underlying causes of crowd disasters and mass fatalities--living readers insight into the root causes of crowd related accidents. It presents a clearer understanding of crowd dynamics and provides the reader with fundamental modeling techniques to plan and manage and improve crowd safely in places of public assembly